Platelet-to-Lymphocyte Ratio in Pediatric Dengue Patients: A Key Indicator of Disease Severity - Silma Farraha; Husni; Deswita Sari; Rikarni; Zelly Dia; Dwi Yulia (HM Publisher, 2025)
Background: Dengue infection remains a significant health concern in Indonesia, with a high mortality rate. Early identification and prediction of severe dengue are crucial for effective management and mortality reduction. The platelet-to-lymphocyte ratio (PLR) has emerged as a potential biomarker for assessing dengue severity due to its association with inflammatory responses. Methods: This descriptive study included 48 pediatric patients diagnosed with dengue hemorrhagic fever (DHF) and dengue shock syndrome (DSS) at Dr. M. Djamil General Hospital Padang between March and August 2024. Patients were included if they were aged 0-18 years, had a confirmed diagnosis of DHF or DSS, and underwent complete blood count and serological testing for dengue. Patients with chronic diseases or other comorbidities were excluded. Complete blood counts were performed using flow cytometry, and PLR was calculated by dividing the platelet count by the absolute lymphocyte count. Clinical data were obtained from medical records. Results: The majority of patients were aged 6-18 years (68.8%), with 20 (41.7%) presenting with DHF and 28 (58.3%) with DSS. The median platelet count was lower in DSS patients (26,000/mm3) compared to DHF patients (35,500/mm3). The median PLR was also significantly lower in DSS patients (8.95) compared to DHF patients (15.61). A PLR value <20 was more frequently observed in DSS patients (89.3%) than in DHF patients (75%). Conclusion: A lower PLR value was associated with more severe clinical manifestations of dengue infection, particularly DSS. PLR can serve as a valuable biomarker for assessing dengue severity, utilizing readily available and cost-effective complete blood count results.